Market share and financial results of insurance companies: The case of the UE-15 countries - Marzanna B. Lament; Sławomir Bukowski (Entrepreneurial Business and Economics Review (EBER), 2024)
Objective: The objective of the article is to examine the relationship between insurance market share and the financial results of insurance companies. We formulated the following research question: Is an insurance company's market position (market share) influenced by its financial results? If so, which ones? Research Design & Methods: The scope of research covers insurance companies operating in the insurance markets of the EU-15 countries. We surveyed the insurance companies with the largest market share. The research period covered the years 2012-2021. We compiled the data on the insurance markets of the EU-15 countries based on the OECD Statistics database and the financial data characterising the insurance companies selected for the study - based on the ORBIS Database. We used STATISTICA 13 and GRETL software to compile the survey results. We used the method of analysis of scientific literature - domestic and foreign, statistical and econometric methods and own observations. Findings: The research has made it possible to answer the research questions. Financial results influence the market position of an insurance company. This means that financial performance was one of the determinants of an insurance company's market position. This is indicated both by the analysis of the literature on the subject, where some studies confirm the existence of a relation between market position, measured by insurance market share, and the financial results of insurance companies and by our research covering the EU-15 insurance market. Implications & Recommendations: The research conducted will serve insurance companies and insurance market institutions - in financial management strategies, as well as by policyholders and beneficiaries of insurance contracts, i.e. consumers - in consumer decision-making. Contribution & Value Added: The study fills a research gap in the determinants of the efficiency of insurance companies and, in particular, the issue of the relation between the market share of a single operator and its financial results. They also contribute to the development of research in insurance finance falling within the discipline of economics and finance. The study of a homogeneous group of insurance companies - with the largest share in a given national market - as well as the study of the insurance market of the EU-15 countries, which should be considered stable with an established market structure, should be regarded as innovative.
Keywords: F3; F4; G2; 330; insurance market; insurance companies; structure of insurance market; results of insurance companies; efficient structure hypothesis; UE-15 countries